Access to mechanical thrombectomy and ischemic stroke mortality in Japan: a spatial ecological study - Ohashi, Kazuki; Osanai, Toshiya; Fujiwara, Kensuke; Tanikawa, Takumi; Tani, Yuji; Takamiya, Soichiro; Sato, Hirotaka; Morii, Yasuhiro; Ogasawara, Katsuhiko (Frontiers in Neurology, 2023)
Background: Advances in stroke treatment have greatly improved outcomes; however, disparities in access to treatment might increase. Achieving equitable access to stroke treatment is a health policy challenge, as rapid treatment is essential for positive outcomes. This ecological cross-sectional study aimed to determine the relationship between the disparities in spatial accessibility to mechanical thrombectomy (SAMT) and stroke mortality rates in Japan, hypothesizing that disparities in SAMT may increase the differences in stroke mortality between regions. Methods: We used the average number of ischemic stroke (IS) deaths between 2020 and 2021 as the response variable; and SAMT, medical resources, and socioeconomic characteristics of each municipality as explanatory variables. A conditional autoregressive model was used to examine the association between the risk of stroke mortality and SAMT. The standardized mortality ratio (SMR) was mapped to understand the nationwide disparities in stroke mortality risk. Results: The median number of IS deaths was 17.5 persons per year in the municipalities (2020 to 2021). The study also found that municipalities with low SAMT were located in the northern part of Japan. The non-spatial regression model results This is a provisional file, not the final typeset article indicated that poor accessibility, a small proportion of bachelor's degrees or higher, and a high proportion of workers in secondary industries were related to high IS mortality. Three models were evaluated using spatial analysis; Model 1 with accessibility indicators alone, Model 2 with medical resources added to Model 1, and Model 3 with socioeconomic characteristics added to Model 2. In Models 1 and 2, the population-weighted spatial accessibility index (PWSAI) showed a significant negative relationship with stroke mortality. However, this was not evident in Model 3. Mapping using Model 3 showed that the high-risk areas were predominantly located in northern Japan, excluding Hokkaido. Conclusion: Access to mechanical thrombectomy was estimated, and regional differences were observed. The relationship between accessibility and IS mortality is unknown; however, regardless of accessibility, municipalities with a high proportion of workers in secondary industries and a small proportion with bachelor's degrees or above are at risk of death from stroke.